PEMBERDAYAAN KOMUNITAS PERIKANAN MELALUI EDUKASI PENGOLAHAN IKAN DAN STRATEGI PEMASARAN BERBASIS POTENSI LOKAL - Yang Gusti Feriyanti; Agna Su’da Wasalma; Berton James Wally; Putriana Sari Sirait (Yayasan Baitul Hikmah al-Zain, 2026)
This community service program aims to strengthen the capacity of fishing communities through education on fish processing and local-based marketing. The program is motivated by the limited processing skills of fishers, which result in the sale of fresh fish at low prices. Field observations indicate that coastal communities possess traditional knowledge in fish processing, such as drying and smoking, yet these techniques have not been adapted to meet modern market demands. The program employed a participatory approach involving fishers, housewives, and coastal youth. Activities included mapping local potential, training on diversified fish products (e.g., fish floss, crackers, nuggets), and providing education on marketing strategies through digital platforms and traditional markets. The training integrated local wisdom, such as traditional methods for maintaining fish quality, enabling participants to adopt innovations more easily. Results indicate a significant improvement in fish processing skills, evidenced by the emergence of new market-ready products. Additionally, cooperative groups were established that utilize social media to market their products while preserving local identity. This program demonstrates that integrating traditional knowledge with modern innovation can enhance the economic independence of fishing communities and realize culturally-based empowerment.